Do Entrepreneurial Competence and Psychological Well-Being Affect Entrepreneurial Interest among Young Entrepreneurs? - Arteurt Yoseph Merung; Iradat Rayhan Sofyan; Nur Andini Sudirman; Andika Isma (Department of Business and Entrepreneurship, Faculty of Economics and Business, Universitas Negeri Makassar, 2024)
This study aims to determine whether entrepreneurial competence affects entrepreneurial interest among young entrepreneurs and whether psychological well-being affects the entrepreneurial interest of young entrepreneurs in Makassar City universities. This research uses a quantitative approach. The population in this study is Makassar State University students who have a business at a young age. The sampling technique to be used in this study is nonprobability sampling. By taking a saturated sample type, the sample obtained is 30 people. The data collection techniques used were observation, questionnaires, and documentation. Analysis of research data using descriptive analysis and multiple regression analysis using the SPSS version 26 program. The results showed that the entrepreneurial competence variable partially had a negative and non-significant effect on the entrepreneurial interest of young entrepreneurs at Makassar State University and the psychological welfare variable partially had a positive and significant effect on the entrepreneurial interest of young entrepreneurs at Makassar State University. Simultaneously (together) entrepreneurial competence and psychological well-being have a positive and significant effect on the entrepreneurial interest of young entrepreneurs.